Theory and practice of model transformations : 9th International Conference, ICMT 2016, held as part of STAF 2016, Vienna, Austria, July 4-5, 2016, Proceedings /: 9th International Conference, ICMT 2016, held as part of STAF 2016, Vienna, Austria, July 4-5, 2016, Proceedings. (2016) - Unknown
No abstract available